Narrative and the politics of identity : the cultural psychology of Israeli and Palestinian youth - Hammack, Phillip L. (New York ; Oxford : Oxford University Press, 2011)
Since the late 19th century, Jews and Arabs have been locked in an intractable battle for national recognition in a land of tremendous significance. This book offers an analysis of the consequences of conflict for the psyche before addressing the mutual constitution of culture and mind through the process of life-story construction.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Youth -- Israel -- Attitudes; Youth -- Palestine -- Attitudes; Identity (Psychology) -- Israel; Identity (Psychology) -- Palestine